2021
DOI: 10.1007/s10875-021-01005-7
|View full text |Cite
|
Sign up to set email alerts
|

A Minimal Parameter Set Facilitating Early Decision-making in the Diagnosis of Hemophagocytic Lymphohistiocytosis

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening immune dysregulation syndrome characterized by uncontrolled immune cell activation. Timely diagnosis is important, since early treatment can improve survival rates. However, completing all assessments needed to reach ≥5 positive criteria out of the 8 HLH-2004 criteria can be time consuming and may delay timely initiation of treatment. Hence, we applied a data-driven approach to identify a minimal parameter set for early decision-making towards the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…To facilitate early diagnosis and treatment of HLH, simplified and rapid diagnostic criteria have been proposed [ 1 ]. A minimal parameter set was developed based on datasets from 5 medical centers in The Netherlands and validated by a dataset from Johns Hopkins Hospital.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To facilitate early diagnosis and treatment of HLH, simplified and rapid diagnostic criteria have been proposed [ 1 ]. A minimal parameter set was developed based on datasets from 5 medical centers in The Netherlands and validated by a dataset from Johns Hopkins Hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening disease that requires rapid diagnosis and treatment. However, the HLH-2004 criteria include tissue biopsy and diagnostic assay for natural killer (NK) cell activity, both of which require time-consuming tests [ 1 ] that may be difficult to perform in a timely manner in clinical practice. In fact, a recent large case series study demonstrated that tissue biopsy was examined in 77 of 101 Egyptian children (76%) with HLH, while NK-cell activity was examined in 0 (0%) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting approach to the diagnosis of HLH was also presented by Smits et al [ 25 ]. The authors divided the HLH 04 criteria into 2 major (splenomegaly, presence of hemophagocytosis in tissue samples) and 3 minor (presence of >1 cytopenia, ferritin concentration >1000 µg/l, and a decrease in fibrinogen concentration with increased triglycerides).…”
Section: Discussionmentioning
confidence: 99%